Neutrinos and Explosive Events in the Universe - Shapiro, Maurice M.; Stanev, Todor; Wefel, John P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This volume contains the Lectures and selected participant contributions to the 14th Course of the International School of Cosmic Rays Astrophysics, a NATO Advanced Study Institute. Well known astrophysicists and astronomers discuss different aspects of the generation of high energy signals in powerful astrophysical objects concentrating on the production of neutrinos and gamma rays from high energy particle interactions. Recent results from new experiments and observatories are presented. Topics cover a wide range including the Spitzer infrared observatory, TeV gamma ray observations, dark matter, and neutrino telescopes. The combination of basic knowledge about the production of high energy signals with information about the data analysis of ongoing observations places the book between the usual levels of a textbook and a conference proceedings. It will give the reader a good introduction to the current field of astroparticle physics, and some of the fascinating astrophysics being addressed.
Outstanding Problems in Particle Astrophysics -- Constructing the Cosmos, from Sunboats to Superclusters -- Recent Results from the Spitzer Space Telescope: A New View of the Infrared Universe -- Beyond the Standard Model in Particle Physics and Cosmology: Convergence or Divergence? -- B-L Genesis: Generalities and Impact on Neutrino Physics -- Stellar Explosion: From Supernovae to Gamma-Ray Bursts -- Close by Compact Objects and Recent Supernovae in the Solar Vicinity -- Supernova Remnants as Cosmic Accelerators -- Radial Distribution of GRBs in Host Galaxies -- Black Holes: Physics and Astrophysics -- The Efficiency of Using Accretion Power of Kerr Black Holes -- Dark Matter: Past, Present, and Future -- On Dynamics of Relativistic Shock Waves with Losses in Gamma-Ray Burst Sources -- The Dynamics of the Carina Spiral Arm -- Magnetic Field Generation and Electron Acceleration in Collisionless Shocks -- High Energy Neutrino Astronomy and Underwater Detectors -- Recent Results from the Milagro Gamma Ray Observatory -- Physics Potential and First Results of the Magic Telescope -- First Results From the H.E.S.S. Cherenkov Telescope System in Namibia -- The AMANDA Neutrino Telescope -- Observation of Very High Energy Gamma Rays from the Remnant of SN 1006 with HEGRA CT1 -- Optical Astronomy with Cherenkov Telescopes -- Status of ANITA and ANITA-lite -- Optical SETI with MAGIC -- Elemental Composition and Propagation of Cosmic Rays at High Energies -- TeV-Scale Gravity: Detecting Black Holes with Cosmic Ray Air Showers -- Ultra High Energy Cosmic Rays: Analysis of Directional Correlations with Astrophysical Sources -- Are Clusters Indicators of the Cosmic Ray Anisotropy? -- Using Cosmic Ray for Monitoring and Forecasting Dangerous Solar Flare Events -- The Knee in the Energy Spectrum of Cosmic Rays -- The Kascade-Grande experiment -- Calibration of the Kascadegrande Hadron Calorimeter at an Accelerator -- The AMS experiment -- Solar Neutron Observation at Ground Level and from Space -- Monte Carlo Simulations and Semianalytical Parameteri-Sations of the Atmospheric Muon Flux -- Measurement of the Fluorescence Yield in Air with the AirLight Experiment.
Keywords: PHYSICS; WEIGHTS AND MEASURES; ASTRONOMY; ASTROPHYSICS; PARTICLES (NUCLEAR PHYSICS).; PARTICLE ACCELERATION; PHYSICS; ASTRONOMY, ASTROPHYSICS AND COSMOLOGY; ELEMENTARY PARTICLES AND NUCLEI; MEASUREMENT SCIENCE, INSTRUMENTATION; EXTRATERRESTRIAL PHYSICS, SPACE SCIENCES; PARTICLE ACCELERATION AND DETECTION, BEAM PHYSICS